Peran Perempuan Pada Resiliensi Anak (Kegiatan Keagamaan) - Habibah, Nur Faiz (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2020)
Activities that are followed by each child in their environment, have an impact that will be remembered until adulthood. The women who surround the children's environment have a role in shaping the character of a child, leading to adolescent life to adulthood. This study aims to explain the resilience of a child in participating in religious activities. In this study, using a naturalistic qualitative approach, with locations in Rejomulyo Hamlet, Sarimulyo Village, Cluring District, Banyuwangi Regency. To collect the data used observation methods and document analysis. In testing the validity of the data, it was measured using the triangulation technique of sources, methods, extending observation time, checking with peers through discussion, and member-checking. Data analysis was carried out by data reduction steps, data display and conclusion drawing. The various kinds of situations and conditions that children have in the environment guided by the intensive role of women in increasing children's resilience are very significant. Children get knowledge about obligations and sunnah in Islamic teachings and also socialize with the environment. A child is able to understand that every problem that every child has has a way to increase resilience so that he is able to overcome every problem at hand. The result of the role of women in accustoming religious activities to children is that they have increased resilience for a child.